The magic - Byrne, Rhonda (Simon & Schuster, |, 2012)
In The Magic, Rhonda Byrne reveals life-changing knowledge about the power of gratitude that was hidden within a two-thousand year old sacred text. Then, on an incredible 28-day journey, she teaches you how to apply this life-changing knowledge in your everyday life, completely transforming every aspect of your life into joy.